(untitled) (European Journal of Behavioral Sciences, 2023)
The use of new social media is common across the world regardless of gender, age group, race, and ethnicity. It plays a significant role in fostering the interconnectedness and development of intercultural relationships as it is not constrained by geographical barriers and is able to promote instant communication between groups or individuals. Communication applications (e.g., WhatsApp) are crucial in enhancing intimacy among individuals residing in different regions. In reflection of the university context, domestic students usually maintain contact with the exchange or international students through digital platforms as they might not have many opportunities for face-to-face interactions upon the completion of the sojourn periods. Therefore, there is discussion on whether social networks and communication applications could help to form and maintain intercultural friendships, and how the relationships might change throughout different stages from the short term to the long run. With the support of prior empirical research, this literature review paper will discuss how communication applications could promote the formation and sustainability of intercultural friendships among college peers in the light of Maslow’s Hierarchy of Needs, the functional model of friendship networks, Social Exchange Theory, and the Contact Hypothesis. It is found that communication applications are significant in forming intercultural relationships as it serves as a way of virtual connection which satisfies the love and belonging needs of Maslow’s Hierarchy and communication with host nationals give better functions on academic and professional aspirations. Yet, the sustainability of relationships depends more on how people weigh the rewards and costs, and the way they utilize the devices to maintain contact over time, hence resulting in the net worth and outcome of a relationship.